Modelagem e imageamento utilizando diferenças finitas - MACEDO, Isadora Augusta Santana de (2020)
Once a mathematical model is chosen in order to simulate a seismic wave propagation, it is possible to perform a Seismic Modeling and a Reverse Time Migration, both numerical simulations based on the reciprocal relations, on the establishing of a mathematical model and on the numerical solution of the acoustic wave equation. This work is a study of the seismic modeling by finite difference schemes, of the stability conditions, simple strategies to reduce the numerical dispersion by the optimization of finite difference operators and also of the theory of the modeling and reverse time migration using the acoustic wave equation. The numerical experiments show how robust is the RTM with respect to errors in the velocity model even in strong lateral velocity variation and the limitation in using this type of migration in velocity analisys.